Test The Ability of Tricoderma harzianum and Bacillus subtilis As Control Agents of Wilted Ralstonia solanacearum Bacteria in Tobacco Plants (Nicotiana tobacum) - Andriani Eko Prihatiningrum; Ahmad Khafids jalaluddin (Universitas Muhammadiyah Sidoarjo, 2020)
This research aims to determine the interaction between Trichoderma harzianum and Bacillus subtilis as controlling bacteria wilting caused by Ralstonia solanacearum bacteria. This research was carried out in Laboratory of Microbiology and Green house at Science and Technology Universitas Muhammadiyah Sidoarjo and has been done on februari until March 2019. This research uses a completely randomized design (RAL) with 11 treatment and 3 replication to obtain 33 experimental units. The variables observed were the onset of symptoms of the dieses, indek of dieeses, stover wet weight planting. Data were ana- lyzed with variety of ANOVA followed by as 5% BNJ. The result of this research indicate that giving Trichoderma harzianum and Bacillus subtilis at the begining and simultane- ously can suppress pathogens than giving pathogens Ralstonia solanacearum first. This research showed the initial appearance of symptoms of dieses different very markedly bud the wet weight of bark and dry weight trimmed cropping showed different not real.